2014
DOI: 10.1007/s10695-014-9981-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel murrel Channa striatus mitochondrial manganese superoxide dismutase: gene silencing, SOD activity, superoxide anion production and expression

Abstract: We have reported the molecular characterization including gene silencing, superoxide activity, superoxide anion production, gene expression and molecular characterization of a mitochondrial manganese superoxide dismutase (mMnSOD) from striped murrel Channa striatus (named as CsmMnSOD). The CsmMnSOD polypeptide contains 225 amino acids with a molecular weight of 25 kDa and a theoretical isoelectric point of 8.3. In the N-terminal region, CsmMnSOD carries a mitochondrial targeting sequence and a superoxide dismu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 71 publications
0
6
0
1
Order By: Relevance
“…The double-stranded RNA (dsRNA) was synthesized with the primers Wnt10b-F3 and Wnt10b-R3 according to the method of Arockiaraj et al [12] (Table 1). Forty-eight male zebrafish were randomly distributed into eight glass tanks.…”
Section: Methodsmentioning
confidence: 99%
“…The double-stranded RNA (dsRNA) was synthesized with the primers Wnt10b-F3 and Wnt10b-R3 according to the method of Arockiaraj et al [12] (Table 1). Forty-eight male zebrafish were randomly distributed into eight glass tanks.…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, the open reading frame (ORF) of GSK-3β gene (NM_131381.1) was cloned with the primers (F1: 5′-CTG GTG AGC AGT AGG GTG-3′; R1: 5′-CGG ATT CGT TCA AGA CAA). According to the method of Arockiaraj et al (2014) , the double-stranded RNA (dsRNA) was synthesized with the primers containing the T7 promoter RNA polymerase recognition sequence at the 5′ end (F2: 5′-GAT CAC TAA TAC GAC TCA CTA TAG GGC GGC ATT CGG CAG CAT GAA AG-3′; R2: 5′-GAT CAC TAA TAC GAC TCA CTA TAG GGG CAC GGC TGT GTC TGG GTC CA-3′). The reactions of in vitro transcription were performed in water at 37°C in a solution containing T7 RNA polymerase (Takara), 100 mM DTT, RNase Inhibitor, 5 × transcription buffer, 2.5 mM rNTP, and the template.…”
Section: Methodsmentioning
confidence: 99%
“…It revealed that the knockdown of MnSOD transcripts is dose‐dependent (Arockiaraj et al . ; Kumaresan et al . ).…”
Section: Molecules Involved In Immune Systemmentioning
confidence: 99%
“…Gene expression of CsMnSOD was analysed through gene silencing studies using interference RNA (RNAi) approach. It revealed that the knockdown of MnSOD transcripts is dose-dependent (Arockiaraj et al 2014d;Kumaresan et al 2015c).…”
Section: Antioxidant Systemmentioning
confidence: 99%